SIAGA BENCANA DENGAN MEMBANGUN RUMAH TAHAN GEMPA (DISASTER PREPARED BY BUILDING AN EARTHQUAKE RESISTANT HOUSE (Universitas Wijayakusuma Purwokerto, 2024)
Natural disasters can occur anytime and anywhere, including in Indonesia. There needs to be anticipatory steps that must be taken to prevent natural disasters from occurring. Efforts to minimize the impact of disasters include building dams, building residential houses or buildings with earthquake-resistant construction. Earthquakes as a natural disaster can have huge impacts that must be experienced by humans. Therefore, there is a need for a deeper understanding regarding the need to plan and build a facility, in this case a residential house which has a building construction structure that is designed to withstand earthquakes that occur on a certain magnitude scale. Residential houses that have a construction structure that is resistant to earthquakes are expected to minimize damage to residential facilities that have been built so that no loss of life occurs. Education from the start regarding natural disasters and their mitigation to the community and providing an understanding of the need to plan and build residential houses that have a building construction structure that is resistant to earthquakes in the form of socialization as a community service activity is carried out so that the community understands how to overcome them by understanding the importance of building a house stand.